Spin-Wave Band Structure in 2D Magnonic Crystals with Elliptically Shaped Scattering Centres - Sławomir Mamica; Maciej Krawczyk; Jarosław Wojciech Kłos (Advances in Condensed Matter Physics)
Spin waves in 2D periodic magnetic nanocomposites are studied by means of the plane wave method. The effect of the ellipticity and in-plane rotation of the scattering centers on the band structure is investigated, to indicate new possibilities of fine tuning of spin-wave filter passbands.